Neuroscience and education in the transition from analog to AI - Michele Di Salvo (Journal of Neuroeducation)
In the last thirty years we have moved from a substantially analogue communication, and education, to an almost completely digital world. We have moved from separate worlds, and competences, to an integrated and interconnected world. The barriers of knowledge and expertise have been broken down, and with them also the principle of mediation and authority in information and knowledge. To fully fulfil our role as educators, we need to make a further effort: to cross the boundary between disciplines and between knowledge. What is needed is a renewed encounter that allows us to merge and blend the new discoveries of neuroscience with the unique and unrepeatable experience of teachers. In a world that appears massified and standardised, we must return to the individuality of the person and grasp that valid element, that useful suggestion, for a model of democratic education that can truly contribute to leaving no one behind and 'no one excluded'. The sea of over-exposure and over-information in which we are all exposed and overexposed would like it to be an opportunity for a free and conscious encounter and confrontation with the other, with what is different from oneself, but in that same sea it is extremely easy and most likely to get lost. This article aims to hint at the recent discoveries of neuroscience regarding emotions, rest, exposure to social media and texting as a prevalent form of communication, regarding reading between paper and screen, for an enhancement of human subjectivity.